Tunnels - Gordon, Roderick (Chicken House/Scholastic, 2008)
When Will Burrows and his friend Chester embark on a quest to find Will's archaeologist father, who has inexplicably disappeared, they are led to a labyrinthine world underneath London, full of sinister inhabitants with evil intentions toward "Topsoilers" like Will and his father.